Alokasi Waktu Kerja Petani di Desa Lawoila Kecamatan Konda Kabupaten Konda - Ale, Suriati; Taufik, Yani; Suriana, Suriana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This research aims to know the time allocation and income earned from mixing farming of both rice field and vegetables farming in the lawoila village of Konda sub-district, South Konawe District, Southeast Sulawesi province. Data were collected from households who carried out mix farming of low land rice field and vegetables which consists of 42 households out of 314 households in Lawoila village. Descriptive analysis has been used to depict the time allocation of the farmers. The results indicate that the time allocation for wet field rice was 3,447 Men’s Working Day and 1,259 Men’s Working Day for vegetables. The high working time allocation in the low land rice field is caused by low land rice field needing the use of machinery and additional manpower (wage labor) whilst vegetable farming used family members as laborers. The time allocation of ‘family workers’ both on the rice field and vegetable farming are more dedicated to raising activities. Through the participant’s time allocation, the income generated by wet rice farming is higher compared to vegetable farming. Farmers cultivate rice and vegetables simultaneously in order to increase their household income whilst utilizing the vacant land surrounding their property for vegetable farming.